Evaluation of the N2O Rate of Change to Understand the Stratospheric Brewer‐Dobson Circulation in a Chemistry‐Climate Model. Issue 22 (13th November 2022) - Minganti, Daniele; Chabrillat, Simon; Errera, Quentin; Prignon, Maxime; Kinnison, Douglas E.; Garcia, Rolando R.; Abalos, Marta; Alsing, Justin; Schneider, Matthias; Smale, Dan; Jones, Nicholas; Mahieu, Emmanuel
Abstract: The Brewer‐Dobson Circulation (BDC) determines the distribution of long‐lived tracers in the stratosphere; therefore, their changes can be used to diagnose changes in the BDC. We evaluate decadal (2005–2018) trends of nitrous oxide (N2 O) in two versions of the Whole Atmosphere Chemistry‐Climate Model (WACCM) by comparing them with measurements from four Fourier transform infrared (FTIR) ground‐based instruments, the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE‐FTS), and with a chemistry‐transport model (CTM) driven by four different reanalyses. The limited sensitivity of the FTIR instruments can hide negative N2 O trends in the mid‐stratosphere because of the large increase in the lowermost stratosphere. When applying ACE‐FTS measurement sampling on model datasets, the reanalyses from the European Center for Medium Range Weather Forecast (ECMWF) compare best with ACE‐FTS, but the N2 O trends are consistently exaggerated. The N2 O trends obtained with WACCM disagree with those obtained from ACE‐FTS, but the new WACCM version performs better than the previous above the Southern Hemisphere in the stratosphere. Model sensitivity tests show that the decadal N2 O trends reflect changes in the stratospheric transport. We further investigate the N2 O Transformed Eulerian Mean (TEM) budget in WACCM and in the CTM simulation driven by the latest ECMWF reanalysis. The TEM analysis shows that enhanced advection affects the stratospheric N2 O trends in the Tropics. While no ideal observational dataset currently exists, this model study of N2 O trends still provides new insights about the BDC and its changes because of the contribution from relevant sensitivity tests and the TEM analysis. Plain Language Summary: The circulation in the stratosphere is characterized by upward motion above the Tropics, followed by poleward and downward motions above the high latitudes. Changes in the pattern of this stratospheric circulation are currently a challenging topic of research. We investigate the decennial changes of this stratospheric circulation using observations and numerical simulations of the long‐lived tracer nitrous oxide. Observations are obtained from ground‐based and satellite instruments. Numerical simulations include complex atmospheric models that reproduce the chemistry and dynamics of the stratosphere. Both observations and models show differences between the hemispheres in the nitrous oxide decennial changes. Unfortunately, the current observations of nitrous oxide are not perfect. The ground‐based instruments cannot correctly measure the changes of nitrous oxide in the northern hemisphere. The satellite does not measure at all times, and it spatially covers more the high latitudes, which negatively affects the measurements of nitrous oxide. On the other hand, model simulations can provide valuable insights into the changes in the stratospheric circulation. They show that changes in the stratospheric circulation cause the differences between hemispheres in the nitrous oxide trends and show that the circulation changes can be associated with different physical processes. Key Points: Sparse sampling of Atmospheric Chemistry Experiment Fourier Transform Spectrometer exaggerates the stratospheric nitrous oxide trends Transformed Eulerian Mean analysis shows that the residual mean advection contributes to the positive nitrous oxide trend in the Tropics The Whole Atmosphere Community‐Climate Model simulates weaker hemispheric asymmetries of the nitrous oxide trends compared to reanalyses